The Change of Immunoactivity of Dendritic Cells Induced by Mouse 4-1BBL Recombinant Adenovirus - Youlin, Kuang (Yonsei University College of Medicine, 2010)
PURPOSE: The purpose of this study is to construct a recombinant adenovirus vector carrying mouse 4-1BBL and observe its effects in dendritic cells. MATERIALS AND METHODS: Mouse 4-1BBL cDNA was taken from the plasmid pcDNA3-m4-1BBL and subcloned into adenovirus shuttle plasmid pAdTrack-CMV, and then transformed into competent BJ5183 with plasmid pAdEasy-1. After recombination in E. coli, Ad-4-1BBL was packaged and amplified in HEK 293 cells. The expression of 4-1BBL in Ad-4-1BBL-transfected mouse prostate cancer cell line RM-1 was detected by reverse transcription polymerase chain reaction (RT-PCR) and Western blot. After the co-culture of dendritic cells (DCs) with Ad-4-1BBL-transfected RM-1 cells, interleukin (IL)-6 and IL-12 production were assessed by enzyme-linked immunosorbent assay (ELISA) and co-stimulatary moleculs (CD80 and CD86) on DCs were analyzed by flow cytometry. RESULTS: The levels of IL-6 (3,960 pg/mL) and IL-12 (249 pg/mL) production in Ad-m4-1BBL-pulsed DCs were more than those in none-pulsed DCs. The differences were statistically significant (p < 0.05). The expression of co-stimulatary molecules (CD80 and CD86) was up-regulated in Ad-m4-1BBL-pulsed DCs. CONCLUSION: The results indicated the recombinant mouse 4-1BBL can effectively activate DCs.